REDUÇÕES UTILIZANDO BOROIDRETO SUPORTADO EM POLÍMERO - Fernandes, Jane Luiza Nogueira (2007)
Reduction reactions of different ketones, such as acetophenone and its derivatives, methylnaphthylketones and heterocyclic ketones were carried out with borohydride supported on polystyrene-divinylbenzene. The most important advantage in using a polymer supported reagent in an organic reaction is the simplification of reaction work-up, i.e. product separation and isolation. The ketones were reduced in good yields. The use of additives such as LiNO3, LiCl, LiBr and LiI to supported borohydride increased significantly the reaction speed of all studied ketones, without diminishing the yield. For the series of acetophenones LiI showed the best result amongst the lithium salts, followed by LiBr. Substituted Acetophenones with a nitro group at positions 3 or 4 were reduced faster than those substituted with amino or methoxy groups at position 4. The analyzed additives increased equally the reduction speed of the methylnaphthylketones. For the series of heterocyclic ketones, LiNO3 presented the best results.